A paleo-neurologic investigation of the social brain hypothesis in frontotemporal dementia. (6th March 2022) - Vandenbulcke, Mathieu; Van de Vliet, Laura; Sun, Jiaze; Huang, Yun-An; Van Den Bossche, Maarten J A; Sunaert, Stefan; Peeters, Ron; Zhu, Qi; Vanduffel, Wim; de Gelder, Beatrice; De Winter, François-Laurent; Van den Stock, Jan
Abstract: The social brain hypothesis posits that a disproportionate encephalization in primates enabled to adapt behavior to a social context. Also, it has been proposed that phylogenetically recent brain areas are disproportionally affected by neurodegeneration. Using structural and functional magnetic resonance imaging, the present study investigates brain–behavior associations and neural integrity of hyperspecialized and domain-general cortical social brain areas in behavioral variant frontotemporal dementia (bvFTD). The results revealed that both structure and function of hyperspecialized social areas in the middle portion of the superior temporal sulcus (STS) are compromised in bvFTD, while no deterioration was observed in domain general social areas in the posterior STS. While the structural findings adhered to an anterior–posterior gradient, the functional group differences only occurred in the hyperspecialized locations. Activity in specialized regions was associated with structural integrity of the amygdala and with social deficits in bvFTD. In conclusion, the results are in line with the paleo-neurology hypothesis positing that neurodegeneration primarily hits cortical areas showing increased specialization, but also with the compatible alternative explanation that anterior STS regions degenerate earlier, based on stronger connections to and trans-neuronal spreading from regions affected early in bvFTD.